Response reduction map for two-degree-of-freedom system with friction - Akinori TOMODA; Ryosuke FUKADA; Tetsuya WATANABE (Nihon Kikai Gakkai ronbunshu, 2014)
This paper deals with the response reduction effect by friction under 2-dof system. The friction behaviour is effective for dissipating seismic energy. Therefore, in recent years, the installation of an isolator and a damper with frictional element in industrial facilities has been investigated. In addition, the seismic response is reduced by the frictional vibration occurring between piping and support system. However, the seismic response of a 2-dof friction system depends on system parameters such as natural frequencies and the mass ratio of the structure by support. A great deal of time is required for non-linear analysis to obtain optimum system parameters. The present study deals with the “Response Reduction Map” for a 2-dof friction system. This map shows the area that the response magnification is less than 1 and less than the response of a linear system. Firstly, the response reduction map by actual seismic wave is shown. Secondly, the response reduction map by the artificial seismic wave calculated from the design spectrum is shown. Optimum friction forces for reducing the seismic response of 2-dof friction system can be easily obtained by this map without non-linear time history analysis.